Advances in botanical research. - Jacquot, Jean-Pierre (Advances in botanical research, 2009)
The field of redox is rapidly changing, specifically in relation to plants where redox reactions are exacerbated compared to non-photosynthetic organisms. The development of proteomics has allowed the identification of hundreds of molecular targets of these systems, and the recent discovery of glutaredoxins ability to bind iron sulphur centers (ISC) and to participate in ISC assembly in other apoproteins has provided many new insights. This volume presents new research on oxidative stress in plants, ranging from the production of reactive oxygen species or reactive nitrogen species, to their accumulation, their involvement in signal transduction, and their degradation, while also covering the links between oxidative stress and biotic and abiotic stresses. * Cutting-edge reviews written from a broad range of scientific perspectives * For over 40 years, series has enjoyed a reputation for excellence * Contributors internationally recognized authorities in their respective fields.